Cloud attenuation statistics from radiometric measurements over a tropical location Kolkata, India. Issue 1 (1st January 2021) - De, Arijit; Maitra, Animesh
Highlights: Ground based radiometer has been used to calculate cloud attenuation. Significant cloud attenuation has been observed over Kolkata in monsoon at 30 GHz. August shows the worst month scenario due to high value of LWP. Cloud attenuation has been compared with rain attenuation. Abstract: The objective of this study is to investigate cloud attenuation at 30 GHz frequency using ground-based microwave radiometric observations at a tropical location, Kolkata. At higher frequencies and lower elevation angles, cloud attenuation is of major concern at a tropical location. The location experiences high value of liquid water path (LWP), which is responsible for cloud attenuation, during the Indian summer monsoon (ISM) and pre-monsoon season. Significant amount of cloud attenuation has been observed during monsoon season at 30 GHz. Two years observations of exceedance probability of cloud attenuation and worst month statistics are presented. The variation of cloud attenuation with frequencies for different elevation angles has also been investigated. The seasonal and diurnal patterns of cloud attenuation are examined. Cloud attenuation, inferred from radiometric measurements before rain commencement, has been compared to rain attenuation at Ku-band. Exceedance probabilities of cloud and rain attenuation have been compared.